Asuhan Keperawatan pada An.M dengan Diagnosa Hipertermi di Ruang Anak Anggrek 1 RSUD dr. Soeselo Kabupaten Tegal - Aerofa Tri Aryani; Esti Nur Janah; Ahmad Zakiudin (Lembaga Pengembangan Kinerja Dosen, 2024)
Fever or hyperthermia is a natural response of the body to fight infections that enter the body and is a sign of an illness. It is said to have a fever if the body temperature exceeds normal body temperature, namely reaching > 37.5°C. The cause of hyperthermia can be due to infectious and non-infectious factors. The World Health Organization (WHO) states that the number of fever cases worldwide ranges between 16 and 33 million, with 500 to 600 thousand deaths per year. The aim of this scientific paper is to provide nursing care to patients with hyperthermia at Dr Soeselo Regional Hospital, Tegal Regency. As a result of the assessment, the patient complained of fever accompanied by coughing, his body temperature reached 39.1°C. Nursing problems that arise are hyperthermia, anxiety and knowledge deficit.